Pengetahuan sebagai Faktor Risiko Kecemasan dalam Pemberian Vaksinasi Covid-19 pada Ibu Hamil - Siregar, Nilda Yulita; Nasution, Eva Mahayani; Sukaisi, Sukaisi; Alfrianne, Alfrianne (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
One of the factors that forms a person's behavior is knowledge. The root cause of anxiety in pregnant women related to the Covid-19 vaccine lies in the lack of knowledge about pregnant women's understanding of the Covid-19 vaccine. How to control anxiety that occurs during pregnancy by helping pregnant women obtain information related to the Covid-19 vaccine. The purpose of this study was to analyze the relationship between knowledge and anxiety about the administration of the Covid-19 vaccine to pregnant women at the Birobuli Health Center, Palu. The design of this study was cross-sectional. All pregnant women at the Birobuli Health Center participated in this study. Knowledge and anxiety were measured by questionnaires, then analyzed using the Chi square test. The results of the analysis showed a p value of 0.000, which means that there was a significant relationship between knowledge and anxiety when administering the Covid-19 vaccine to pregnant women at the Birobuli Health Center. The conclusion drawn is that knowledge is a risk factor for anxiety when administering the Covid-19 vaccine to pregnant women at the Birobuli Health Center, Palu.Keywords: Covid-19; vaccination; knowledge; anxiety ABSTRAK Salah satu faktor terbentuknya perilaku seseorang adalah pengetahuan. Akar penyebab kecemasan pada ibu hamil terkait vaksin Covid-19 terletak pada kurangnya pengetahuan tentang pemahaman ibu hamil terhadap vaksin Covid-19. Cara mengendalikan kecemasan yang terjadi selama kehamilan dengan cara membantu ibu hamil memperoleh informasi terkait vaksin Covid-19. Tujuan penelitian ini adalah menganalisis hubungan antara pengetahuan dengan kecemasan terhadap pemberian vaksin Covid-19 pada ibu hamil di Puskesmas Birobuli, Palu. Rancangan penelitian ini adalah cross-sectional. Semua ibu hamil di Puskesmas Birobuli berpartisipasi dalam penelitian ini. Pengetahuan dan kecemasan diukur dengan kuisioner, lalu dianalisis dengan uji Chi square. Hasil analisis menunjukkan nilai p adalah 0,000, yang berarti bahwa ada hubungan yang signifikan antara pengetahuan dengan kecemasan saat pemberian vaksin Covid-19 pada ibu hamil di Puskesmas Birobuli. Kesimpulan yang diambil adalah bahwa pengetahuan merupakan faktor risiko kecemasan saat pemberian vaksin Covid-19 pada ibu hamil di Puskesmas Birobuli, Palu.Kata kunci: Covid-19; vaksinasi; pengetahuan; kecemasan